Government attitude and attention allocation on ecological governance in the context of vertical intergovernmental relations - LU Liangdong, XU Zhengjian, WEI Jiuchang, XU Jia (Ziyuan Kexue, 2023)
[Objective] Because the decision-making process of the government follows the principle of “satisfaction” rather than “optimization”, attitude becomes a key element in the decision-making process. From this perspective, this study examined how the ecological governance attitude of higher-level government acts on the attention allocation of lower-level governments. [Methods] Based on the topic model and machine learning techniques, this study examined 3648 provincial and municipal government work reports (2010-2021) sentence by sentence. Then the ecological governance attitude and attention allocation of the provincial and municipal governments were measured and analyzed. [Results] The study found that the ecological governance attitude of higher-level governments can directly and indirectly act on the attention allocation of lower-level governments, and the ecological governance attitude of lower-level governments themselves plays a mediation role in the process. There are differences in the influence of different attitudes on attention. The increase of negative attitude of higher-level governments towards ecological governance significantly improves the attention allocation of lower-level governments, indicating the “deterrent effect” of negative attitude; while the improvement of the positive attitude of higher-level governments reduces the attention allocation of lower-level governments, which indicate the competitive relationship and “crowding out effect” of different issues on local governments’ attention. The results were also verified through robustness tests, including measuring government attention by governance data on the Internet, and testing the “attitude-attention” relationship under the issue of “production safety”. [Conclusion] This article argued that the government should pay attention to the role of government attitude as a management signal, and take the expression framework of government attitude as an important management tool, to reasonably regulate the attention allocation of ecological governance of local governments.